Divalent Nonaqueous Metal-Air Batteries - Lu, Yi-Ting; Neale, Alex R.; Hu, Chi-Chang; Hardwick, Laurence J. (Frontiers in Energy Research, 2021)
In the field of secondary batteries, the growing diversity of possible applications for energy storage has led to the investigation of numerous alternative systems to the state-of-the-art lithium-ion battery. Metal-air batteries are one such technology, due to promising specific energies that could reach beyond the theoretical maximum of lithium-ion. Much focus over the past decade has been on lithium and sodium-air, and, only in recent years, efforts have been stepped up in the study of divalent metal-air batteries. Within this article, the opportunities, progress, and challenges in nonaqueous rechargeable magnesium and calcium-air batteries will be examined and critically reviewed. In particular, attention will be focused on the electrolyte development for reversible metal deposition and the positive electrode chemistries (frequently referred to as the “air cathode”). Synergies between two cell chemistries will be described, along with the present impediments required to be overcome. Scientific advances in understanding fundamental cell (electro)chemistry and electrolyte development are crucial to surmount these barriers in order to edge these technologies toward practical application.